2021
DOI: 10.1038/s41598-021-90339-8
|View full text |Cite
|
Sign up to set email alerts
|

Low serum adiponectin level is associated with better physical health-related quality of life in chronic kidney disease

Abstract: Hyperadiponectemia is paradoxically associated with renal disease progression and mortality in chronic kidney disease (CKD). Its association with health-related quality of life (HR-QOL) is unknown. This study aimed to verify the association between adiponectin and HR-QOL in Korean pre-dialysis CKD cohort. This cross-sectional study analyzed 1551 pre-dialysis CKD patients from KNOW-CKD (KoreaN Cohort Study for Outcome in Patients With Chronic Kidney Disease). Participants were categorized into three tertiles (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…Our finding in the current study is contrary to the previous reports from the general population with CAD ( 8 10 ), where low serum adiponectin level has been suggested as a predictor of CAC. The results in this study are rather in accordance with previous studies ( 14 16 ) that demonstrated the adiponectin paradox. A fundamental question to the adiponectin paradox is whether the biological action of adiponectin is actually altered in a context-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our finding in the current study is contrary to the previous reports from the general population with CAD ( 8 10 ), where low serum adiponectin level has been suggested as a predictor of CAC. The results in this study are rather in accordance with previous studies ( 14 16 ) that demonstrated the adiponectin paradox. A fundamental question to the adiponectin paradox is whether the biological action of adiponectin is actually altered in a context-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…A study targeting the association of adipokines with blood pressure in rural Chinese adolescents reported that adiponectin was negatively associated with SBP only in men ( 13 ). Mounting evidence also suggests that chronic kidney disease (CKD) should alter the clinical interpretation of serum adiponectin level, as low serum adiponectin is associated with better health-related quality of life in a cohort study of patients with pre-dialysis CKD ( 14 ). Another study from the same cohort also reported the increased risk of anemia development with high serum adiponectin ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was reported that in CKD, a better physical health-related quality of life is associated with low circulating adiponectin levels [ 26 ]. The high adiponectin levels may reflect or mediate the wasting and malnutrition state that is common in this disease.…”
Section: Adiponectinmentioning
confidence: 99%